Stroke Volume Variation-Guided Goal-Directed Fluid Therapy Did Not Significantly Reduce the Incidence of Early Postoperative Complications in Elderly Patients Undergoing Minimally Invasive Esophagectomy: A Randomized Controlled Trial - Tang, Wei; Qiu, Yuwei; Lu, Huijie; Xu, Meiying; Wu, Jingxiang (Frontiers in Surgery, 2021)
Study Objective This study aimed to investigate whether stroke volume variation (SVV)-guided goal-directed therapy (GDT) can improve postoperative outcomes in elderly patients undergoing minimally invasive esophagectomy (MIE) compared with conventional care. Design A prospective, randomized, controlled study. Setting A single tertiary care center with a study period from August 2017 to December 2018. Patients Patients over 65 years old who were scheduled for elective MIE. Interventions The GDT protocol included a baseline fluid supplement of 7 ml/kg/h Ringer's lactate solution and SVV optimization using colloid boluses assessed by pulse-contour analysis (PiCCO™). When SVV exceeded 11%, colloid was infused at a rate of 50 ml per minute; if SVV returned below 9% for at least 2 minutes, then colloid was stopped. Measurements The primary outcome was the incidence of postoperative complications before discharge, as assessed using a predefined list, including postoperative anastomotic leakage, postoperative hoarseness, postoperative pulmonary complications, chylothorax, myocardial injury and all-cause mortality. Main Results Sixty-five patients were included in the analysis. The incidence of postoperative complications between groups was similar (GDT 36.4% vs control 37.5%, P = 0.92). The total fluid volume was not significantly different between the two groups (2192 ± 469 ml vs 2201 ± 337 ml, P = 0.92). Compared with those in the control group (n = 32), patients in the GDT group (n = 33) received more colloids intraoperatively (874±369 ml vs 270 ± 67 ml, P < 0.05) and less crystalloid fluid (1318 ± 386 ml vs 1937 ± 334 ml, P < 0.05). Conclusion: GDT does not reduce the incidence of early postoperative complications after minimally invasive esophagectomy in elderly patients.